Squamous cell carcinoma of tympanomastoid region – A rare and often misdiagnosed entity - Singla, Anshul; Garg, Uma; Singla, Bhavika; Garg, Amit (International Journal of Research in Medical Sciences, 2017)
Squamous cell carcinoma of the temporal bone and external auditory canal is a rare entity. We present a case of 62 year old male, with stage IV squamous cell carcinoma of tympanomastoid region. As the tumour was deemed unresectable, mass debulking was done and patient was given post-operative radiotherapy. The objective to report this case was to emphasise the importance of early diagnosis and prompt treatment for a better survival. A high index of suspicion is necessary as the initial presentation may mimic more common otologic conditions.